Effect of Nitrogen Doping on Optical and Photocatalytic Properties of TiO2 Thin Film Prepared by Spin Coating Process - Wanichaya Mekprasart; Thanakorn Khumtong; Jiravat Rattanarak; Wicharn Techitdheera; Wisanu Pecharapa (My University, 2013)
Nitrogen-doped TiO2 thin films were prepared by spin coating on glass substrate. Different amount of nitrogen doped in TiO2 matrix was 0, 3 and 10%. As-obtained films were annealed at 400 °C for 2 h. The optical and photocatalytic properties of N-doped TiO2 thin films were analyzed via UV-Vis spectrophotometry. The chemical properties were investigated by Fourier transform infrared spectrometer and Raman spectroscopy. When doping TiO2 with nitrogen, its absorption spectrum is shifted to visible region resulting to the enhancement of photocatalyst properties in dye photodegradation. Raman and FTIR patterns show that N-doped TiO2 pattern is still identical to undoped TiO2 pattern resulting to unsubstitutation of nitrogen atom in Ti-O bonding.
Keywords: Spin Coating; Photodegradation; TiO2 Photocatalysis and Solar Cells